Street Furniture Influence in Revitalizing the Bahraini Identity - Islam Hamdi El-Ghonaimy (Journal of Contemporary Urban Affairs, 2020)
Bab Al-Bahrain Avenue is one of the liveliest streets and its location is in the intermediate of the historical part that gave the avenue a strong historical dimension in the urban context of Manama city, Kingdom of Bahrain. Moreover, the avenue has economic and cultural significance activities. The socio-economic value of Bab-AL Bahrain and the gold market make them the busiest streets in Manama. The existing users of the avenue are variable between residences, local visitors and tourist. Unfortunately, with the rapid urban developing for the Manama City in general and Bab Al Bahrain area, and the changing for the economic base for most of the original families they moved to other suitable places to them while new non-Bahraini replaced them. As a result, the sense of identity and belonging is not considerable. Consequently, the identity for these areas is in its way to disappear. This research analyzed the street furniture condition and focused on the act of street furniture role in revitalizing Bahraini identity in such an area. Moreover, the research draws the point of revitalizing the sense of belonging for the residences, which will influence positively upon the open spaces’ conditions and the visual quality.